Keberagaman dalam Masyarakat Multikultural di Indonesia: Kajian atas Pemikiran Bikhu Parekh - Sahira, Emilia; Utami, Aulia Asri; Aprilianata, Aprilianata (Journal of Civic Education, 2025)
Indonesia is a nation marked by remarkable cultural diversity, encompassing thousands of ethnic groups and regional languages. In navigating this complexity, Bhikhu Parekh’s theoretical framework on multiculturalism offers a compelling lens through which to examine the challenges and opportunities of managing pluralism. His principles—emphasizing recognition, respect, intercultural dialogue, justice, and unity in diversity—align closely with the foundational values of Pancasila, Indonesia’s state ideology. Despite this alignment, the practical implementation of multiculturalism in Indonesia remains fraught with challenges, including persistent social inequality, cultural tensions, and human rights concerns. This article critically explores these issues through the case studies of Papua and Aceh. It proposes several policy recommendations, including stronger recognition of local identities, sustained intercultural dialogue, reinforcement of social justice, and the expansion of multicultural education. These measures aim to foster national cohesion, reduce interethnic conflict, and promote inclusive development for all Indonesian citizens.